Papel da Ética e da Moral na formação de Engenheiros e Tecnólogos de Alimentos: o caso da UTFPR/Medianeira - Arruda, Marisa Bernardete Ribas [UNESP] (2015)
It addresses the Ethics issues involving engineers and technologists in food in the development of professional practice. For such, in a critical analysis, we developed a theoretical study in order to rethink the teaching of ethics, which seeks Well rational action of man, starting from the interest in providing human development training courses these professionals, offered by a public university technology. In a socio-historical perspective, we sought to advance the knowledge accumulated, emphasizing the characteristic relation of vocational training to Ethics, finding safe refuge in the work Nicomachean Ethics, Aristotle, to think about human action. Given the comprehensive training of engineers and technologists in food, as appropriate model to be based on strategic education, was chosen as Aristotelian ethics to guide the connection between the individual and collective levels of moral development, providing subsidies for the improvement of higher education as a place of professional, committed to the construction of socially meaningful knowledge. It is concluded from that reflective reading, which can be formed in man, a provision through habit, members of the choice determined by the logos in the field of many possibilities. Forasmuch as it is possible that training occur with engineers and technologists seeking graduation in UTFPR, Campus of Medianeira.